Ancrage au sol et (nouvelles) mobilités dans l’espace saharo-sahélien : des expériences similaires et compatibles - Charles Grémont (L’Année du Maghreb)
Since the 1980s, the so-called ‘nomadic’ populations of northern Mali and Niger have increasingly become sedentary. At the same time, individuals or small groups among these populations have considerably extended their spatial mobility. Although these two processes might at first appear contradictory, empirical investigations show instead that they are complementary and respond to similar rationales. Building on recent works in human geography and sociology, this article suggests that the creation of villages and other permanent settlements result from rationales of mobility. The notion of mobility here does not only refer to moving in space, but rather to a way of relating to others and being in the world